2010
DOI: 10.1097/ccm.0b013e3181d9d9fe
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a family support intervention on family satisfaction, length-of-stay, and cost of care in the intensive care unit

Abstract: The implementation of the family support coordinator intervention increased family satisfaction across a range of parameters. Although there were decreases in length-of-stay and costs, they were not statistically significant. Further research is needed to determine whether intervention refinement could produce lower length-of-stay and costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
75
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(80 citation statements)
references
References 23 publications
1
75
0
2
Order By: Relevance
“…Shelton et al (34) evaluated the effect of adding a full-time family support coordinator to a surgical ICU team in a pre-post study design; no differences in LOS were observed in the pre versus postimplementation period (11.8 d vs 11.4 d, respectively, p = 0.89). In a patient-targeted intervention, Daly et al (35) enrolled patients from five different ICUs and evaluated the effectiveness of an intensive communication strategy in a pre-post design; there were no significant differences in ICU LOS (13.4 d vs 14.4 d, pre vs post, respectively; p = 0.16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Shelton et al (34) evaluated the effect of adding a full-time family support coordinator to a surgical ICU team in a pre-post study design; no differences in LOS were observed in the pre versus postimplementation period (11.8 d vs 11.4 d, respectively, p = 0.89). In a patient-targeted intervention, Daly et al (35) enrolled patients from five different ICUs and evaluated the effectiveness of an intensive communication strategy in a pre-post design; there were no significant differences in ICU LOS (13.4 d vs 14.4 d, pre vs post, respectively; p = 0.16).…”
Section: Resultsmentioning
confidence: 99%
“…Third, intervention targets varied between studies (patient vs system). For example, two of the trials reporting no difference in LOS involved system-level interventions with patient-level outcomes, which could potentially attenuate the effect seen on ICU LOS (27, 34). For these reasons, we separated interventions by setting and level of the intervention target.…”
Section: Discussionmentioning
confidence: 99%
“…Various approaches to improve the communication and decision-making have been presented recently. Shelton et al [63 ] showed that the introduction of a family support coordinator increased family satisfaction in their ICU. As the authors point out, the main task of the coordinator was to serve as liaison between the patient's family and the healthcare team.…”
Section: Communication and Decision-makingmentioning
confidence: 98%
“…In a multi-center cluster RCT conducted by Curtis et al, a quality improvement intervention targeted at hospitals and clinicians to integrate palliative care in the ICU also did not result in a significant decrease in LOS (18). Shelton et al evaluated the effect of adding a full-time family support coordinator to a surgical ICU team in a pre-post study design; no differences in LOS were observed in the pre versus post-implementation period (19). Lastly, Daly et al enrolled patients from 5 different ICUs and evaluated the effectiveness of an intensive communication strategy involving proactive multidisciplinary family conferences using a pre-post design; there were no significant differences in ICU LOS (20).…”
Section: Studies Reporting On Icu Losmentioning
confidence: 99%